Czym jest kulturologia? - Kasperski, Edward (Załącznik Kulturoznawczy, 2023)
Culturology as a distinct reflection of culture that emerged in the second half of the twentieth century, and the so-called cultural turn in the humanities (the turn that realised their cultural background and base) became the impetus for its development. The article tries to clarify what is the term in question, the subject of its research, what kind of theoretical assumptions does it make in relation to this subject and what specific learning goals does it face. One of the key question of culturology concerns culture: what are its limits, how its forms may vary in space and time, and whether or to what extent they form − despite differences − a community, unity and totality. The article indicates the dynamic, processual and creative nature of culture on one hand, and its openness on the other, consequently proving the utopian character of aspirations willing to establish once and for all an unchangeable ʻessenceʼ of culture as well as its timeless determinants and systemic framework. The article consists of three parts: 1) Context, subject and properties of culturology, 2) Delimitations of culture, 3) Acceleration, literacy, multiculturalism, culturalism